Improving public sector service delivery: a developing economy experience. Issue 7 (10th September 2018) - Adaku, Ebenezer; Amoako-Gyampah, Kwasi; Lomotey, Seth Nii Anang; Amoatey, Charles Teye; Famiyeh, Samuel
Abstract : Purpose: The Pension Trust Company (PTC) in Ghana is the sole agency responsible for the management of the first-tier pension scheme as well as processing of claims submitted by beneficiaries for this scheme. The claim processing system at PTC was wrought with significant delays resulting in severe customer dissatisfaction and hardship to retirees. Hence, a new system – Age 54 + project – was developed to address the problems related to claims processing. The purpose of this paper is to report on the efficiency gains from the new claim processing system implemented at PTC and to use the philosophies behind the lean operations concept to explain the results. Design/methodology/approach: Data for this study were obtained from the benefits system of PTC for the period 2009–2013. The data consist of a series of benefits processing time for two groups of 56, 000 claimants – those cleared under the Age 54 + project and those cleared under the old processing system. The processes of the two claim processing systems were analysed and their processing times compared. Findings: The new system – Age 54 + – decreased the average processing time for new claims by 20 per cent. The new system is a simple approach which is driven by a "Let's Start in Time" idea. Originality/value: The operations management literature suggests that process redesign approaches and the implementation of continuous improvement techniques represent mechanisms for achieving performance improvements at governmental agencies. This study shows and discusses the redesign of a social security scheme process using a lean operation concept of waste elimination method and application of kanban to deliver performance improvement.